Epididymis and testis of the bird: Literary review - Franzo, Vanessa Sobue; Vulcani, Valcinir Aloisio Scalla (Pubvet, 2015)
The epididymis of birds is functionally important in sperm transport and maturation, secretion and reabsorption of fluid and the removal of degenerate sperm. In birds, this structure has no anatomical subdivisions in head, body and tail, as occurs in mammals. There are differences regarding the presence of microvilli associated with the transport of sperm between the bird species.